Care and occupational therapy: what kind of care definition do we have?/Cuidado e Terapia Ocupacional: que tipo de definição de cuidado nós temos? - Serrata Malfitano, Ana Paula; Sakellariou, Dikaios (Cadernos Brasileiros de Terapia Ocupacional, 2019)
Care can mean different things to different people. Often, it is understood as referring to professional actions associated with an individualistic approach. In the context of healthcare, it is usually understood as a professional action, referring to service provision. In occupational therapy, the definition of care is not well explored. Drawing on sociological and anthropological literature, we performed a non-systematic literature review to problematize the definition of care and its application in occupational therapy. Defining care as an expression of social support, a fundamental attribute for maintaining life and the basis for the development of essential components of social life, we discuss four of its dimensions: the biomedical, the person-centred, the tacit, and the collective. We argue that occupational therapy, historically, has been aligned with biomedical care and has made moves towards the person-centred dimension. We argue that occupational therapists should explore ways to articulate all four care dimensions of care to inform their practice.